2020
DOI: 10.1107/s205252061901494x
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate crystal structure of PbHfO3

Abstract: Controversy in the description/identification of so-called intermediate phase (s) in PbHfO 3 , stable in the range $420-480 K, has existed for a few decades. A synchrotron diffraction experiment on a partially detwinned crystal allowed the structure to be solved in the superspace group Imma(00)s00 (No. 74.2). In contrast to some previously published reports, in the pure compound only one distinct phase was observed between Pbam PbZrO 3 -like antiferroelectric and Pm3m paraelectric phases. The modulation vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 22 publications
8
27
0
2
Order By: Relevance
“…97 It was recently reported that this system also has an INC structural transition (Figure 12B,C). 112 Niobate perovskites such as NaNbO 3 and AgNbO 3 have multiple octahedral tilt transitions. Near room temperature, there is an AFE phase that has the orthorhombic space group Pbcm, with the antipolar distortions coming from the Nb-O bonds.…”
Section: Perovskite Structure and Afementioning
confidence: 99%
See 1 more Smart Citation
“…97 It was recently reported that this system also has an INC structural transition (Figure 12B,C). 112 Niobate perovskites such as NaNbO 3 and AgNbO 3 have multiple octahedral tilt transitions. Near room temperature, there is an AFE phase that has the orthorhombic space group Pbcm, with the antipolar distortions coming from the Nb-O bonds.…”
Section: Perovskite Structure and Afementioning
confidence: 99%
“…[96]). (B,C) Representation of the incommensurate modulations in the structure of PbHfO 3 , after Bosak et al 112 (B) The Pb atoms (shown as dark circles) are modulated predominantly in the [110] of the cubic prototype group. (C) the structure also has an octahedral tilt [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Crystal Structures and Crystallography Of Afesmentioning
confidence: 99%
“…В монокристаллах чистого PZO СЭ-фаза существует в очень узком температурном интервале [3,4], в то время как в керамиках цирконата свинца промежуточная СЭ-фаза наблюдается в довольно широкой температурной области [5]. В зависимости от концентрации компонентов в твердых растворах и от внешних условий в соединениях группы PZO наблюдается большое разнообразие структурных состояний, включая упомянутые АСЭ и СЭ фазы [6] фазы, а также несоразмерные структуры [7,8]. Структура АСЭ-фаз хорошо изучена; обнаружено сосуществование двух параметров порядка -собственно антисегнетоэлектрического, характеризуемого волновым вектором q = (1/4 1/4 0) и антиферродисторсионного, характеризуемого волновым вектором q R = (1/2 1/2 1/2).…”
Section: Introductionunclassified
“…В работе [8] приведены результаты расшифровки несоразмерной структуры PbHfO 3 . В тоже время однозначное решение структуры СЭ-фазы PZT с x ≤ 0.06 по прежнему отсутствует несмотря на большое число работ посвященных этой проблеме [9][10][11][12].…”
Section: Introductionunclassified
“…473 K. Several publications were devoted to establishing the proper structure of this phase. [16][17][18] Based on the latest findings, the symmetry of this phase was established to be orthorhombic, with IC modulations and with Imma(00γ)s00 super-space group. 18 However, the problem of mechanisms responsible for the phase transitions observed is still subject to investigation.…”
Section: Introductionmentioning
confidence: 99%